2022
DOI: 10.3389/fonc.2022.829212
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adenylate Cyclase Family: New Concept of Targeted Cancer Therapy

Abstract: The adenylate cyclase (ADCY) superfamily is a group of glycoproteins regulating intracellular signaling. ADCYs act as key regulators in the cyclic adenosine monophosphate (cAMP) signaling pathway and are related to cell sensitivity to chemotherapy and ionizing radiation. Many members of the superfamily are detectable in most chemoresistance cases despite the complexity and unknownness of the specific mechanism underlying the role of ADCYs in the proliferation and invasion of cancer cells. The overactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…cAMP as a secondary messenger promotes proliferation, migration, metabolism, and invasion of cancer cells, and most importantly, it may be a potential suppressor of apoptosis [ 120 , 121 ]. It has also been shown that many upregulated proteins in cancer cells can promote cAMP production [ 122 , 123 , 124 ]. Using the analysis of transcriptome data, Yue et al [ 16 ] have demonstrated that in patients with BRCA1 deficient ovarian cancer the cAMP pathway is significantly activated, which is associated with increased expression of the ADRB1, β-adrenoreceptor genes.…”
Section: Signal Transduction Pathways As Potential Therapeutic Targetsmentioning
confidence: 99%
“…cAMP as a secondary messenger promotes proliferation, migration, metabolism, and invasion of cancer cells, and most importantly, it may be a potential suppressor of apoptosis [ 120 , 121 ]. It has also been shown that many upregulated proteins in cancer cells can promote cAMP production [ 122 , 123 , 124 ]. Using the analysis of transcriptome data, Yue et al [ 16 ] have demonstrated that in patients with BRCA1 deficient ovarian cancer the cAMP pathway is significantly activated, which is associated with increased expression of the ADRB1, β-adrenoreceptor genes.…”
Section: Signal Transduction Pathways As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Schizonts grown in PHHs treated with forskolin (adenylate cyclase activator) or LDN193189 (inhibitor of Bone Morphogenic Protein pathway) are the relatively smaller with lower PfMSP1 expression. In forskolin treated schizonts, activated adenylate cyclase leads to increased levels of cAMP which in turn can activate the Wnt pathway[37, 38]. However, the relationship between the BMP pathway (LDN193189) and the Wnt pathway is less obvious as the former can either inhibit or activate the Wnt pathway depending on the presence of wildtype of p53 or the loss of SMAD4 respectively [39].…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of each of these genes in their respective disorder(s) is described in detail in the subsequent sections. The pathway and some of these cancers have also been the subject of several recent reviews ( 29 , 30 ).…”
Section: Wide Variation In the Biology And Clinical Features Of Camp-...mentioning
confidence: 99%
“…To date, both targeted (i.e., gene-specific) and whole-exome sequencing approaches have yielded few candidates. One study has identified potentially deleterious nonsynonymous single nucleotide polymorphisms (nsSNPs) in ADCY6 as a prognostic or therapeutic target, but the findings have yet to be confirmed by other groups and the role of these mutations in tumorigenesis has yet to be determined ( 30 ). Further whole-exome sequencing of diverse tumor types, followed by functional analysis of the mutations identified in these screens, are necessary before we can conclude that adenylyl cyclase mutations are truly capable of acting as driver mutations in human cancer.…”
Section: Wide Variation In the Biology And Clinical Features Of Camp-...mentioning
confidence: 99%